Cytisus scoparius link - A natural antioxidant - Bandyopadhyay Arun; Saha Bishnu; Mukherjee Kakali; Venkatesan Kumar; Haja Nazeer; Sundararajan Raja; Mukherjee Pulok (BMC, 2006)
Abstract Background Recent investigations have shown that the antioxidant properties of plants could be correlated with oxidative stress defense and different human diseases. In this respect flavonoids and other polyphenolic compounds have gained the greatest attention. The plant Cytisus scoparius contains the main constituent of flavone and flavonals. The present study was undertaken to evaluate the in vitro antioxidant activities of extract of aerial part of Cytisus scoparius. Methods The plant extract was tested for DPPH (1, 1-diphenyl, 2-picryl hydrazyl) radical scavenging, nitric oxide radical scavenging, superoxide anion radical scavenging, hydroxyl radical scavenging, antilipid peroxidation assay, reducing power and total phenol content. Results The extract exhibited scavenging potential with IC50 value of 1.5 μg/ml, 116.0 μg/ml and 4.7 μg/ml for DPPH, nitric oxide and superoxide anion radicals. The values were found to lesser than those of vitamin C, rutin, and curcumin, as standards. The extract showed 50% protection at the dose of 104.0 μg/ml in lipid peroxidation induced by Fe2+/ ascorbate system in rat liver microsomal preparation. There is decrease in hydroxyl radical generation with IC50 value of 27.0 μg/ml when compared with standard vitamin E. The reducing power of the extract depends on the amount of extract. A significant amount of polyphenols could be detected by the equivalent to 0.0589 μg of pyrocatechol from 1 mg of extract. Conclusion The results obtained in the present study indicate that hydro alcoholic extract of aerial part of Cytisus scoparius is a potential source of natural antioxidants.